La historia de la arqueología uruguaya bajo la lupa: recolecciones, donaciones e intercambios de objetos en Cabo Polonio y Valizas (1885-1991) - Blasco Alvarez, Jimena (2025)
This paper presents the temporal and spatial extension of the different practices of collecting and forming collections of materials with archaeological interest from Cabo Polonio and Valizas, two towns in the department of Rocha, located on the Atlantic coast of Uruguay. Many important personalities and scientific societies in the development of Uruguayan archaeology have visited the study area. They were responsible for the formation of important public collections. From the survey of archives and oral information, different practices emerged which, in addition to collecting, involved donations and exchanges for money, favours and consumer goods. The participation of various people who have been made invisible in the story that archaeology has told about itself also emerged. The results are discussed in terms of the current tensions between professional archaeologists and collectors.